Investigating the effectiveness of whole-virus, protein-based, and vector-based SARS-CoV-2 vaccines on the rates of COVID-19 infection, hospitalization, and mortality: a historical cohort study in Iran - Davoud Tanbakuchi; Nadiasadat Taghavi Razavizadeh; Maryam Salari; Ehsan Mosa Farkhani; Mohammad Taghi Shakeri; Seyed Saeed Tabatabaee; Rasoul Raesi; Vahid Ghavami (BMC Infectious Diseases)
Abstract Background Each of the Coronavirus disease 2019 (COVID-19) vaccines has its characteristics that can affect their effectiveness in preventing hospitalization and patient mortality. The present study aimed to determine the effectiveness of COVID-19 vaccines, including whole-virus, protein-based, and vector-based on COVID-19 infection, hospitalization, and mortality. Methods The current cohort study was conducted using the data of all people who received at least two doses of each type of COVID-19 vaccine from March 2020 to August 2022 in Khorasan Rzavi province. Quantitative data were characterized using measures of central tendency and dispersion, while the risks of infection, hospitalization, and mortality were assessed for each type of vaccine. Logistic regression was employed to evaluate the effect of various vaccine types on infection rate, hospitalization, and mortality while adjusting for other independent variables. Results In this study, over 2 million vaccinated individuals had received at least two doses of the COVID-19 vaccine. Whole-virus vaccines, which had an infection rate of 3%, a hospitalization rate of 1.4%, and a mortality rate of 0.2%, were the most effective vaccines. The study also identified several factors associated with an increased risk of COVID-19 infection, hospitalization, and mortality, including kidney disease, cardiovascular disease, respiratory issues, age, sex, diabetes, olfactory dysfunction, fever, chills, body mass index (BMI), and the type of vaccine. Conclusion This study highlights the substantial impact of COVID-19 vaccination in reducing infection, hospitalization, and mortality rates in Iran. The results support the use of whole-virus and vector-based vaccines as more effective options for preventing COVID-19 outcomes. The study also emphasizes the importance of considering various factors, including medical history and side effects, when evaluating the effectiveness of different vaccine types. The findings of this study can inform public health policy and vaccination strategies in Iran and other countries.